Chemical characterization of Pseudomonas veronii 2E soluble exopolymer as Cd(II) ligand for the biotreatment of electroplating wastes - Ferreira, Maria Laura (2017)
The production, isolation, purification and characterization of soluble Extracellular Polymeric Substances (EPS) secreted by Pseudomonas veronii 2E were studied. Optimal production was obtained in medium M9-14 g l-1 glycerol, 25 °C. Spectrophotometric and potentiometric titration studies showed that EPS consisted on extracellular DNA, proteins and polysaccharides as the main components. DNase I, Proteinase K and further sodium deoxycholate treatments yielded similar proportions of lipopolysaccharides (LPSs) and exopolysaccharides (ExPs). ExP was subjected to total acid hydrolysis and then analyzed by High Performance Anion Exchange Chromatography with Pulsed Amperometric Detection (HPAEC-PAD), showing the presence of fucose, galactosamine, glucosamine, galactose, glucose, mannose and glucuronic acid. Further treatment with oxalic acid confirmed the presence of a pyruvilated sugar. The ability of the secreted products to interact with Cd(II) was studied by anodic stripping voltammetry (ASV). LPS fraction contained the highest ligand concentration (279 ± 10 µmoles Cd(II) binding sites g LPS-1). This information is a valuable tool for the application of EPS in industrial wastewater treatment.